Histological study of Culex pipiens pipiens larvae and adults infected with Beauveria bassiana - Baghdad Science Journal (مجلة بغداد للعلوم, 2012)
This study aimed to show the histological changes that 0ccured in Culex pipiens pipiens larvae and adults infected with Beauveria bassiana . The 4th instar larvae and adult mosquitoes were infected with B.bassiana in 10-4 spore/ml dilution, after 96 hours histological section was studied showing that the fungi infected all the body parts specially Cuticle , Epiderms, fat bodies and midgut. After 120 hours of exposure to the fungi the insect have a white appearance and covered with a thick coat of hyphea. Thus study shows biological control of B .bassiana on mosquitoes.